Experience of Music Used With Psychedelic Therapy: A Rapid Review and Implications. (30th March 2020) - O'Callaghan, Clare; Hubik, Daniel J; Dwyer, Justin; Williams, Martin; Ross, Margaret
Abstract: Bonny Method of Guided Imagery and Music emerged following discontinuation of psychedelic therapy research in the early 1970s, but psychedelic therapy research has since revived. Music remains a vital component. This study examined participants' experiences of music in psychedelic therapy research. A rapid review of qualitative and quantitative journal articles in four major databases was conducted in February to April, 2019, using the terms hallucinogens, psychedelic, "lysergic acid diethylamide, " psilocybin, ayahuasca, music, and/or "music therapy." Of 406 articles retrieved, 10 were included ( n = 180; 18–69 years old). Participants had varied backgrounds. Music was widely considered integral for meaningful emotional and imagery experiences and self-exploration during psychedelic therapy. Music transformed through its elicitation of anthropomorphic, transportive, synesthetic, and material sensations. Music could convey love, carry listeners to other realms, be something to "hold, " inspire, and elicit a deep sense of embodied transformation. Therapeutic influence was especially evident in music's dichotomous elicitations: Music could simultaneously anchor and propel. Participant openness to music and provision of participant-centered music were associated with optimal immediate and longer-term outcomes. Many studies reported scarce details about the music used and incidental findings of music experienced. Further understanding of participants' idiosyncratic and shared responses to music during drug therapy phases will inform optimal development of flexible music protocols which enhance psychedelic therapy. Music therapists could be involved in the psychedelic therapy research renaissance through assisting with research to optimize music-based protocols used. If psychedelics become approved medicines, music therapists may be involved in offering psychedelic therapy as part of therapeutic teams.